Positive electrode active material for lithium ion secondary battery and lithium ion secondary battery

By using lithium-nickel composite oxide with a hexagonal crystalline layered structure in a lithium-ion secondary battery, the secondary particle structure formed by a single primary particle and multiple primary particles is solved, and the poor circulation characteristics of lithium-nickel composite oxide are solved. The problem of battery expansion achieves higher circulation characteristics and thermal stability.

CN114342122BActive Publication Date: 2024-12-13SUMITOMO METAL MINING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202080060892.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-08-28
Publication Date
2024-12-13
Estimated Expiration
2040-08-28

AI Technical Summary

Technical Problem

The lithium-nickel composite oxide has poor circulation characteristics in lithium-ion secondary batteries, and the problems of gas generation and battery expansion due to repeated charging and discharge are difficult to effectively solve the problem of prior art.

Method used

Using lithium-nickel composite oxide with a hexagonal crystalline layered structure, the secondary particles formed by the condensation of individual primary particles and multiple primary particles, controls the difference in the mass ratio of the metal element and the cross-sectional crystal plane orientation of the particles to control the difference in the cross-sectional crystal plane orientation of the particles to Improve cycle characteristics.

Benefits of technology

The circulation characteristics of lithium-ion secondary batteries are significantly improved, gas generation and battery expansion are reduced, and thermal stability and capacity maintenance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114342122B_ABST
    Figure CN114342122B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel composite oxide, wherein the lithium nickel composite oxide has a hexagonal layered structure and is composed of at least one of a single primary particle and a secondary particle formed by agglomeration of a plurality of primary particles, wherein the metal elements constituting the lithium nickel composite oxide include lithium (Li) and nickel (Ni) and arbitrarily include at least one element M (M) selected from the group consisting of Co, Mn, Al, V, Mg, Mo, Ca, Cr, Zr, Ti, Nb, Na, K, W, Fe, Zn, B, Si, P and Ta, wherein the amount ratio of the metal elements is represented by Li:Ni:M=a:b:c (wherein 0.95≤a≤1.10, 0.30≤b≤1.00, 0.00≤c≤0.70, b+c=1), and wherein the cross section of the particles contained in the positive electrode active material has one or more crystal planes, and the average orientation difference of the crystal planes relative to a reference direction is within 0.7°.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a lithium ion secondary battery. Background Art

[0002] In recent years, with the popularization of portable electronic devices such as mobile phones and notebook personal computers, there is a strong desire to develop small and lightweight non-aqueous electrolyte secondary batteries with high energy density and durability. In addition, as batteries for power tools and electric vehicles represented by hybrid vehicles, there is a strong desire to develop high-output secondary batteries.

[0003] As secondary batteries that meet such requirements, there are non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. Lithium ion secondary batteries using lithium metal composite oxides with layered or spinel crystal structures as positive electrode active materials can obtain high voltages of 4V, and are therefore being promoted for practical use as batteries with high energy density.

[0004] As a lithium metal composite oxide, lithium cobalt composite oxide (LiCoO) which is relatively easy to synthesize has been proposed. 2 ), using lithium nickel composite oxide (LiNiO 2 ), lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ), lithium manganese composite oxide (LiMn 2 O 4 ), lithium nickel manganese composite oxide (LiNi 0.5 M 0.5 O 2 )wait.

[0005] Among them, lithium nickel composite oxides have attracted attention in recent years as materials with high energy density that can realize secondary batteries with high battery capacity without using cobalt, a resource with a small amount of storage. However, lithium nickel composite oxides have the following problems compared with other lithium metal composite oxides: the problem of battery capacity decreasing with repeated discharge, that is, the problem of poor cycle characteristics, and the problem of large battery expansion caused by gas generation during repeated charge and discharge.

[0006] Lithium nickel composite oxides are generally composed of secondary particles formed by agglomeration of a plurality of primary particles. One of the reasons for the deterioration of the cycle characteristics of secondary batteries with repeated charge and discharge is the rupture, deformation or destruction of secondary particles due to expansion and contraction during charge and discharge (see Patent Documents 1 and 2).

[0007] The secondary particles are believed to break from the interface (grain boundary) between the primary particles. Therefore, it is expected that the cycle characteristics can be improved by reducing the interface between the primary particles in the lithium nickel composite oxide, that is, by forming the lithium nickel composite oxide with secondary particles formed by a single primary particle or a small number of primary particles agglomerated.

[0008] For example, Patent Document 1 proposes a lithium transition metal composite oxide for a lithium secondary battery positive electrode active material, wherein primary particles are aggregated to form secondary particles, and the ratio of the average particle size of the secondary particles to the average particle size of the primary particles is greater than 1 and less than 5. According to Patent Document 1, it is believed that when used as a positive electrode active material, based on the above-mentioned effect, a lithium transition metal composite oxide capable of suppressing the cycle degradation of a lithium secondary battery accompanied by repeated charge and discharge will be obtained.

[0009] In addition, Patent Document 2 proposes a positive electrode active material for a non-aqueous secondary battery, characterized in that it is a powdery lithium composite oxide having monodisperse primary particles mainly composed of one element selected from the group consisting of Co, Ni, and Mn and lithium, with an average particle size (D50) of 3 to 12 μm and a specific surface area of ​​0.2 to 1.0 m 2 / g, volume density is 2.1g / cm 3 The inflection point of the volume reduction rate based on the Cooper Plot method is 3 ton / cm 2 According to Patent Document 2, it is believed that by controlling the lithium composite oxide as the primary particles, a positive electrode active material and a positive electrode for a non-aqueous secondary battery composed of primary particles can be provided which maintain high volume density and battery characteristics without worrying about cracking.

[0010] In addition, Patent Document 3 provides a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, which comprises: preparing a 90% particle size of a cumulative particle size distribution based on a volume basis; 1 D 90 With 10% particle size 1 D 10 than 1 D 90 / 1 D 10The process of preparing a composite oxide particle containing nickel having a molar ratio of 3 or less and containing nickel; the process of obtaining a raw material mixture containing the composite oxide particles and a lithium compound and having a ratio of the total molar number of lithium to the total molar number of metal elements contained in the composite oxide being 1 or more and 1.3 or less; the process of heat-treating the raw material mixture to obtain a heat-treated product; the process of dispersing the heat-treated product in a dry manner to obtain a first dispersion; and the process of contacting the first dispersion with a liquid medium to obtain a second dispersion, wherein the positive electrode active material comprises lithium transition metal composite oxide particles, and the lithium transition metal composite oxide particles have a 50% particle size of a cumulative particle size distribution based on a volume basis obtained by electron microscope observation. 2 D 50 The average particle size 2 D SEM Ratio 2 D 50 / 2 D SEM is 1 or more and 4 or less, and has a composition represented by the following formula (1).

[0011] Li p Ni x Co y M 1 z O 2+α (1)

[0012] (In formula (1), p, x, y, z and α satisfy 1.0≤p≤1.3, 0.6≤x<0.95, 0≤y≤0.4, 0≤z≤0.5, x+y+z=1 and -0.1≤α≤0.1, M 1 represents at least one of Mn and Al. )

[0013] According to Patent Document 3, it is thought that an effective production method for obtaining a positive electrode active material including lithium transition metal composite oxide particles composed of a single particle or in which the number of primary particles constituting one secondary particle is reduced can be provided.

[0014] In addition, Patent Document 4 proposes a positive electrode active material for a non-aqueous electrolyte secondary battery, which comprises a lithium transition metal composite oxide particle group, wherein the average particle size D of the lithium transition metal composite oxide particle group as observed by an electron microscope is SEM The 50% particle size D in the cumulative particle size distribution based on volume is 1 μm or more and 7 μm or less. 50 The ratio of the average particle size obtained by electron microscope observation to D 50 / D SEM The 90% particle size D in the cumulative particle size distribution based on volume is 1 or more and 4 or less. 90 With 10% particle size D 10 Ratio D90 / D 10 The lithium transition metal composite oxide contains nickel in its composition and has a layered structure. According to Patent Document 5, it is believed that a positive electrode active material for a non-aqueous electrolyte secondary battery having both high output characteristics and high durability can be provided.

[0015] In addition, Patent Document 5 proposes a positive electrode active material for a secondary battery, which includes a lithium nickel composite oxide having a layered rock salt structure and a composition formula of Li x Ni y M z O 2 (Wherein, M is at least one metal element selected from the group consisting of Co, Al, Mg, Ca, Cr, Mo, Si, Ti and Fe, and x, y and z satisfy 0.95≤x≤1.05, 0.8≤y≤1, 0≤z≤0.2 and y+z=1, respectively.) It indicates that the half-value width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern is less than 0.13°, and the content of positive electrode active material with a particle size of less than 3.41 μm is less than 2 volume % relative to the total amount of positive electrode active material contained in the positive electrode.

[0016] According to patent document 5, it is believed that the particle size of the single crystal particles of the layered oxide in cited document 5 with a half-value width n of less than 0.13° is sufficiently large and has a size that can be directly used as a positive electrode active material. Therefore, there is no risk of reduced durability due to particle rupture that exists in secondary particles formed by agglomeration of primary particles. By using the layered oxide with a half-value width n of less than 0.13° as a positive electrode active material, a secondary battery with further improved durability can be manufactured.

[0017] Prior art literature

[0018] Patent Literature

[0019] Patent Document 1: Japanese Patent Application Publication No. 2001-243949

[0020] Patent Document 2: Japanese Patent Application Publication No. 2004-355824

[0021] Patent Document 3: Japanese Patent Application Publication No. 2017-188444

[0022] Patent Document 4: Japanese Patent Application Publication No. 2017-188445

[0023] Patent Document 5: International Publication No. 2017 / 169129 Summary of the invention

[0024] Problems to be solved by the invention

[0025] Patent Documents 1 to 5 describe improving cycle characteristics by controlling the number of primary particles, particle size, particle size distribution, etc. constituting lithium metal composite oxides. However, further improvement in cycle characteristics is required in secondary batteries using lithium nickel composite oxides as positive electrodes.

[0026] The present invention has been made in view of such circumstances, and an object of the present invention is to provide a positive electrode active material for a lithium ion secondary battery, which is a positive electrode active material containing a lithium nickel composite oxide and has improved cycle characteristics when used in a positive electrode of a secondary battery.

[0027] Methods for solving problems

[0028] In a first embodiment of the present invention, a positive electrode active material for a lithium ion secondary battery is provided, which includes a lithium nickel composite oxide, the lithium nickel composite oxide having a hexagonal layered structure and consisting of at least one of a single primary particle and a secondary particle formed by agglomeration of a plurality of primary particles, the metal elements constituting the lithium nickel composite oxide comprising lithium (Li) and nickel (Ni) and arbitrarily comprising at least one element M (M) selected from the group consisting of Co, Mn, Al, V, Mg, Mo, Ca, Cr, Zr, Ti, Nb, Na, K, W, Fe, Zn, B, Si, P and Ta, the amount ratio of the metal elements being represented by Li:Ni:M=a:b:c (wherein 0.95≤a≤1.10, 0.30≤b≤1.00, 0.00≤c≤0.70, b+c=1), the cross section of the particles contained in the positive electrode active material having one or more crystal planes, and the average orientation difference of the crystal planes relative to a reference direction is within 0.7°.

[0029] In addition, the number ratio of the single primary particles is preferably 50% or more relative to the total number of particles. In addition, the (003) diffraction peak intensity I obtained by X-ray diffraction measured using Cu-kα rays as an X-ray source and a flat sample holder of a Bragg-Brentano optical system is (003) and (104) diffraction peak intensity I (104) The ratio (I (003) / I (104) ) is preferably 2.0 or more. In addition, the volume-based median diameter (D50) is 10 μm or less, and the average primary particle size of the lithium nickel composite oxide is preferably 0.3 μm or more. In addition, the specific surface area determined by the nitrogen adsorption method is preferably 1.0 m 2 / g above 5.0m 2 / g or less.

[0030] In a second aspect of the present invention, there is provided a lithium ion secondary battery comprising at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode contains the positive electrode active material for a lithium ion secondary battery.

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a positive electrode active material for a lithium ion secondary battery having improved cycle characteristics when used in a positive electrode of a secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] [ Figure 1 ] Figure 1 This is a SEM observation picture of the cross section of the positive electrode active material of Example 10.

[0034] [ Figure 2 ] Figure 2 is for Figure 1 The GROD map of the particle located in the center indicated by the arrow is obtained by measuring the EBSD method.

[0035] [ Figure 3 ] Figure 3 This is a SEM observation picture of the cross section of the positive electrode active material of Comparative Example 7.

[0036] [ Figure 4 ] Figure 4 is for Figure 3 The GROD map of the particle located in the center indicated by the arrow is obtained by measuring the EBSD method.

[0037] [ Figure 5 ] Figure 5 This is a schematic diagram of a button-type battery used in battery evaluation.

[0038] [ Figure 6 ] Figure 6 This is a schematic diagram of a laminated battery used in battery evaluation. DETAILED DESCRIPTION

[0039] Hereinafter, a positive electrode active material for a lithium ion secondary battery and a method for producing the same, and a lithium ion secondary battery using the positive electrode active material according to the present embodiment will be described.

[0040] 1. Positive electrode active material for lithium-ion secondary batteries

[0041] The positive electrode active material for lithium ion secondary battery of the present embodiment (hereinafter also referred to as "positive electrode active material") comprises a lithium nickel composite oxide containing at least lithium and nickel. The lithium nickel composite oxide is composed of at least one of a single primary particle and a secondary particle formed by agglomeration of a plurality of primary particles. The positive electrode active material of the present embodiment has improved cycle characteristics when used for the positive electrode of a secondary battery. Below, the composition of the positive electrode active material of the present embodiment is described in detail.

[0042] [Lithium Nickel Composite Oxide]

[0043] (primary particles, secondary particles)

[0044] The lithium nickel composite oxide of the present embodiment has a hexagonal layered structure and is composed of at least one of a single primary particle and a secondary particle formed by agglomeration of a plurality of primary particles. The lithium nickel composite oxide may be composed of only a single primary particle, only a secondary particle, or both a single primary particle and a secondary particle.

[0045] The number ratio of the single primary particles is preferably 30% or more, more preferably 50% or more, and further preferably 70% or more relative to the total particles of the lithium nickel composite oxide. It goes without saying that the number ratio of the single primary particles can be 90% or more, or 100%. It should be noted that when the number ratio of the primary particles is 100%, it means that the lithium nickel composite oxide is composed of only single primary particles.

[0046] Furthermore, the number of primary particles constituting the secondary particles of the lithium nickel composite oxide is preferably small. Specifically, the number of primary particles constituting the secondary particles is preferably 15 or less, and more preferably 10 or less.

[0047] It should be noted that the number ratio of individual primary particles is calculated as follows: for more than 100 lithium nickel composite oxide particles contained in the positive electrode active material, it is determined whether it is composed of individual primary particles or secondary particles (agglomerated from multiple primary particles), and the ratio of the number of particles determined as individual primary particles to the total number of particles determined (total number of particles) is calculated. It should be noted that for the determination of which of the primary particles or secondary particles the particles are composed of, it is preferred to perform cross-section processing on the particles of the lithium nickel composite oxide, and use a scanning electron microscope (SEM) observation diagram of the particle cross section (hereinafter, also referred to as "SEM diagram") for observation. Although it can also be confirmed roughly by the SEM diagram of the particle shape, this may lack accuracy.

[0048] For example, Figure 1 is a SEM image of a cross section of particles contained in the positive electrode active material of Example 10 described later. Figure 3 : is a SEM image of a cross section of particles contained in the positive electrode active material of Comparative Example 7 described later. Figure 1 As shown, the positive electrode active material of this embodiment includes individual primary particles (arrows).

[0049] In addition, the determination of individual primary particles or secondary particles can also be performed using the band contrast of the electron backscatter diffraction (hereinafter sometimes referred to as EBSD) method, or it can be performed using a focused ion beam (FIB) processing device during cross-section processing. In this case, it can also be confirmed using an observation image of the particle cross section obtained based on the accompanying scanning ion microscope (SIM).

[0050] (Constituent elements)

[0051] The elements constituting the lithium nickel composite oxide include at least lithium (Li) and nickel (Ni). In addition, as an arbitrary element (M), at least one element selected from the group consisting of Co, Mn, Al, V, Mg, Mo, Ca, Cr, Zr, Ti, Nb, Na, K, W, Fe, Zn, B, Si, P and Ta may be included. In addition, a small amount of elements other than the above elements may be included.

[0052] The amount ratio (molar ratio) of the elements other than oxygen constituting the lithium nickel composite oxide is represented by Li:Ni:M=a:b:c (where 0.95≤a≤1.10, 0.30≤b≤1.00, 0≤c≤0.70, b+c=1). The content ratio of each element is described below.

[0053] (lithium)

[0054] In the above-mentioned amount ratio, the value of a representing the amount ratio of Li corresponds to the amount ratio (Li / Me ratio) of Li and the above-mentioned element Me (ie, Ni and M) other than lithium. In the above-mentioned amount ratio, the range of a is 0.95≤a≤1.10. When the range of a is the above-mentioned range, the reaction resistance of the positive electrode is reduced and the output of the secondary battery is improved. When the value of a is less than 0.95 or greater than 1.10, the reaction resistance may become larger and the output of the battery is reduced. In addition, the range of a can be 0.97≤a≤1.05.

[0055] (nickel)

[0056] In the above-mentioned amount ratio, the range of b representing the amount ratio of Ni is 0.30≤b≤1.00. When the value of b is in the above-mentioned range, a high battery capacity can be obtained, and high cycle characteristics can be obtained. In addition, from the viewpoint of further improving the battery capacity, the range of b can be 0.70 or more, for example, 0.70≤b<0.95. In addition, when b is 1.00, high cycle characteristics can also be obtained.

[0057] (Element M)

[0058] In the above-mentioned amount ratio, the element (M) is at least one selected from Co, Mn, Al, V, Mg, Mo, Ca, Cr, Zr, Ti, Nb, Na, K, W, Fe, Zn, B, Si, P and Ta. In addition, in the above-mentioned amount ratio, the range of c representing the amount ratio of the element M is 0.00≤c≤0.70, preferably 0.02≤c≤0.50, and more preferably 0.10≤c≤0.30. The type of element (M) can be appropriately selected according to the required battery characteristics.

[0059] For example, the element M may contain at least Co. When the amount ratio of Co contained in c in the above amount ratio is denoted as c 1 In the case of 1 The range is 0<c 1 ≤0.30, preferably 0.02≤c 1 ≤0.25, more preferably 0.05≤c 1 ≤0.20. 1 When the value of is within the above range, high thermal stability and output characteristics can be achieved.

[0060] Furthermore, the element M may contain at least Mn. When the amount ratio of Mn contained in c in the above amount ratio is defined as c 2 In the case of 2 The range is preferably 0<c 2 ≤0.30, more preferably 0.02≤c 2 ≤0.25, more preferably 0.05≤c 2 ≤0.20. When c2 is in the above range, thermal stability can be improved.

[0061] Furthermore, the element M may contain at least Al. When the amount ratio of Al contained in the above amount ratio c is set to c 3 In the case of 3 The range is preferably 0<c 3 ≤0.10, more preferably 0.01≤c 3 ≤0.08, more preferably 0.01≤c 3 ≤0.06. 3 When the range is within the above range, thermal stability can be improved.

[0062] The composition of the lithium nickel composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) emission spectrometry.

[0063] [Strain within the particle]

[0064] In the particles of lithium nickel composite oxide contained in the positive electrode active material of this embodiment, the crystal grains constituting the particles are low strain. The magnitude of the strain is considered to be positively correlated with the magnitude of the orientation difference between the reference crystal orientation and the actual orientation, and specifically, it can be inferred by analyzing the cross section of the lithium nickel composite oxide particles using GROD (Grain Reference Orientation Deviation) of the EBSD (Electron Backscatter Diffraction) method.

[0065] For example, Figure 1 and Figure 3 FIG. 1 is a diagram showing a SEM observation image of a cross section of particles contained in the positive electrode active material of Example 10 and Comparative Example 7 described later, Figure 2 and Figure 4 They are shown respectively Figure 1 and 3 Figure GROD diagram of a particle (cross section) indicated by an arrow. Figure 4 , Figure 6 In the GROD diagram shown, when measuring the crystal orientation, the face of one crystal plane is set (the region where the crystal orientation difference is within 15°), and the direction shown in the crystal plane is used as the reference (reference direction), and the difference (angle) between the direction shown in each measurement point in the same plane as the crystal plane and the reference direction is visualized by color. It should be noted that the cross section of the particles contained in the positive electrode active material has one or more crystal planes. Furthermore, if the analysis range is set to one particle, information such as the average value and distribution of the orientation difference within the particle can be obtained.

[0066] For example, in Figure 2 In the particle shown (single primary particle), except for a part of the surface layer, almost no orientation difference relative to the reference direction is detected, and the strain is very small. Figure 4 In the cross section of the particle (secondary particle) shown, a plurality of crystal planes having large orientation differences with respect to the reference direction (that is, crystal grains having large strain) are observed, and therefore the average orientation difference of the entire particle is also large.

[0067] In the particles of the positive electrode active material of the present embodiment, the average orientation difference of the crystal plane relative to the reference direction is preferably within 0.7°, more preferably within 0.6°, and further preferably within 0.5°. If the average value of the orientation difference is greater than 0.7°, it means that there are many regions with large orientation differences, i.e., regions with high strain, in the particles. It is believed that such regions have a high probability of becoming the starting point of rupture due to the expansion and contraction of the crystals produced by the insertion and detachment of Li, and thus the cycle characteristics are reduced as a result. It should be noted that since it is ideal that there is no difference with the reference direction, the lower limit of the average value of the orientation difference is 0. In addition, the average orientation difference in the particles contained in the positive electrode active material refers to the value obtained by averaging the average value of the orientation difference of each crystal plane in a plurality of particles (e.g., more than 10) contained in the positive electrode active material using a plurality of particles.

[0068] [Peak intensity ratio of (003) plane to (104) plane]

[0069] The lithium nickel composite oxide contained in the positive electrode active material of this embodiment has a hexagonal layered structure. Therefore, when the positive electrode active material is measured using the powder X-ray diffraction method (hereinafter sometimes also referred to as "XRD"), diffraction peaks belonging to the (003) plane and the (104) plane are obtained.

[0070] In the positive electrode active material of the present embodiment, in the X-ray diffraction pattern measured using a flat sample holder of the Bragg-Brentano optical system, the diffraction peak intensities (hereinafter, each also referred to as “I (003) ” and “I (104) ".) is the ratio of (003) / I (104) The value of is 2.0 or more, more preferably 2.2 or more. (003) / I (104) When the value of is within the above range, the crystal structure is less disordered and the packing property of the positive electrode active material is improved, so the cycle characteristics are improved.

[0071] The diffraction peak intensity is not only affected by the crystal growth in the direction perpendicular to the surface as the object, but also by the orientation of the sample filled in the sample holder. Especially in the measurement using a flat sample holder, the diffraction peak intensity is easily affected by the selective orientation due to the shape (crystal shape) of the sample filled in the flat sample holder. Here, the filling property of the lithium nickel composite oxide particles in the flat sample holder is positively correlated with the filling property in the electrode (positive electrode) formed by coating the flat collector. It is believed that the improvement of the filling property of the sample in the flat sample holder indicates that the positive electrode active material in the positive electrode will form a high filling. Therefore, the I measured using a flat sample holder is (003) / I (104) The value of is not only the ratio of crystal growth in the direction perpendicular to the (003) plane and the (104) plane, but also serves as an indicator of filling properties including when the positive electrode is formed. (003) / I (104) When the value of is less than 2.0, the packing property is reduced and the effect of improving the cycle characteristics may not be seen.

[0072] The diffraction peaks can be determined from an X-ray diffraction pattern measured with CuKα rays using an XRD diffractometer (for example, Empyrean manufactured by Malvern Panalytical).

[0073] [Median diameter (D50)]

[0074] The volume-based median diameter (D50) of the positive electrode active material of the present embodiment is 10.0 μm or less, preferably 0.3 μm or more and 10.0 μm or less, preferably 1.0 μm or more and 10.0 μm or less, more preferably 1.2 μm or more and 8.0 μm or less, and further preferably 1.5 μm or more and 8.0 μm or less. It should be noted that the median diameter (D50) can be obtained, for example, from the volume cumulative value measured by a laser diffraction scattering particle size distribution analyzer.

[0075] [Average primary particle size]

[0076] The average primary particle size constituting the lithium nickel composite oxide is 0.3 μm or more, and can be 1.0 μm or more. In addition, the upper limit is a value that is the same as or smaller than the median diameter (D50). By setting the median diameter (D50) to the above range, and setting the average particle size of the primary particles to the above range, it is possible to have sufficiently large primary particles and obtain a positive electrode active material with reduced crystal grain boundaries. It should be noted that the average primary particle size is calculated as follows, that is, the SEM observation image of the particles (appearance) of the lithium nickel composite oxide is subjected to image analysis, and the major axis length of the primary particles where the overall image of the particles can be observed at more than 5 locations is measured, and calculated from the average value thereof.

[0077] [Specific surface area]

[0078] The specific surface area of ​​the positive electrode active material of this embodiment measured by the BET method is preferably 1.0 m 2 / g above 5.0m 2 / g or less. If the specific surface area is less than 1.0m 2 / g, the number of reaction sites where lithium ions can enter and exit is reduced, so the charge capacity and discharge capacity may be reduced. The upper limit of the specific surface area is not particularly limited, but in the positive electrode active material of this embodiment, the upper limit is 5.0m 2 / g or so.

[0079] [Amount of dissolved lithium]

[0080] The amount of lithium dissolved in water when the positive electrode active material is immersed in water (hereinafter, also referred to as "the amount of dissolved lithium"). For example, it can be 0.8% by mass or less relative to the positive electrode active material as a whole, and can be 0.5% by mass or less. In addition, from the viewpoint of suppressing gas generation, the amount of dissolved lithium is more preferably 0.30% by mass or less, and further preferably 0.15% by mass or less. By making the amount of dissolved lithium the above range, in addition to improving the cycle characteristics described above, the gas generation in the secondary battery can also be suppressed. The range of the lower limit of the amount of dissolved lithium is not particularly limited, for example, even if it is 0.05% by mass or more, gas generation can be fully suppressed. The amount of dissolved lithium can be reduced, for example, by containing Zr as an element (M) or by washing described later.

[0081] 2. Method for producing positive electrode active material for lithium ion secondary battery

[0082] The method for producing the positive electrode active material for lithium ion secondary batteries is not particularly limited as long as a positive electrode active material having the above-mentioned characteristics can be obtained. An example of the method for producing the positive electrode active material of the present embodiment will be described below.

[0083] The method for producing a positive electrode active material according to the present embodiment may include, for example, a mixing step ( S10 ) of mixing a nickel composite compound and a lithium compound to obtain a mixture, and a calcining step ( S20 ) of calcining the mixture to obtain a lithium nickel composite oxide.

[0084] Furthermore, the element (M) other than nickel may be added as a compound of the element (M) in the mixing step ( S10 ), or a nickel composite compound containing the element (M) may be used.

[0085] [Mixing step (S10)]

[0086] The mixing step (S100) is a step of mixing the nickel composite compound and the lithium compound to obtain a mixture. In addition, a compound of the element (M) is mixed as needed. The nickel composite compound, the lithium compound, and the compound of the element (M) as needed can be added and mixed in the form of powder (solid phase), for example. Each material is described below.

[0087] (Nickel complex compound)

[0088] The nickel composite compound used in the mixing step (S10) can be obtained by a known method. The content (composition) of the metal (Ni, Co and other elements (M)) in the nickel composite compound is also substantially maintained in the lithium nickel composite oxide particles, so the content of each element is preferably in the same range as the content in the above-mentioned lithium nickel composite oxide. It should be noted that the nickel composite compound used in this embodiment can contain a small amount of elements other than the above-mentioned elements (Ni, Co and other elements (M)), hydrogen and oxygen within the range that does not hinder the effect of the present invention.

[0089] The nickel composite compound can be a hydroxide or an oxide. As a method for manufacturing a nickel composite hydroxide, for example, a method for neutralizing and crystallizing using an aqueous solution of a metal salt and an alkaline solution can be cited. In addition, the nickel composite compound can also be heat-treated to remove the water in the nickel composite compound, or a part or all of the nickel composite compound can be made into a nickel composite oxide.

[0090] (Lithium compounds)

[0091] The lithium compound is not particularly limited, and known compounds containing lithium can be used, for example, lithium carbonate, lithium hydroxide, lithium nitrate or a mixture thereof can be used. Among them, lithium carbonate, lithium hydroxide or a mixture thereof are preferably used from the viewpoint that the influence of residual impurities is small and it is easy to dissolve at the calcination temperature. In addition, lithium hydroxide is more preferably used from the viewpoint that a lithium nickel composite oxide with high crystallinity is obtained.

[0092] (Hybrid Method)

[0093] The mixing method of the nickel composite compound, the lithium compound and the compound of the element (M) as needed is not particularly limited, as long as the particles are fully mixed to the extent that the skeleton of these particles is not destroyed. As a mixing method, for example, a conventional mixer can be used for mixing, for example, a vibration mixer, a Lodige mixer, a Julia mixer, a V-type blender, etc. can be used for mixing. In the case of insufficient mixing, sometimes there is a deviation in the atomic % ratio (Li / Me) of the element Me other than Li between each particle of the positive active material, and it is impossible to obtain sufficient battery characteristics.

[0094] The lithium compounds are mixed in such a manner that the Li / Me in the mixture becomes greater than 0.95 and less than 1.10. That is, the mixture is mixed in such a manner that the Li / Me in the mixture becomes the same as the Li / Me in the obtained calcined product. This is because the molar ratio of Li / Me and each element does not change before and after the calcining step (S20), so the Li / Me of the mixture in the above-mentioned mixing step (S10) will become the Li / Me of the calcined product. It should be noted that the content (ratio) of the elements in the mixture is also substantially maintained in the lithium nickel composite oxide. It should be noted that, in the case of implementing the water washing described later, the Li / Me in the mixture can also be adjusted to be higher than the above range in consideration of the amount of excess lithium to be removed.

[0095] [Firing step (S20)]

[0096] The calcining step (S20) is a step of calcining the mixture obtained in the mixing step (S10) to obtain a calcined product of a lithium nickel composite oxide. When the mixture is calcined, the lithium in the lithium compound diffuses into the nickel composite compound to form a calcined product of a lithium nickel composite oxide. The lithium compound melts at the temperature during calcination and penetrates into the nickel composite compound to form a calcined product of a lithium nickel composite oxide.

[0097] The firing atmosphere is preferably carried out in an oxidizing atmosphere, and the oxygen concentration may be 80% by volume or more, preferably 85% by volume or more. In addition, the holding temperature for firing is preferably 700° C. or more and 1000° C. or less. When firing at the above temperature, the crystallinity of the lithium nickel composite oxide becomes higher, and the battery capacity can be further increased.

[0098] The holding time at the calcination temperature is preferably 3 hours or longer, more preferably 5 hours or longer and 24 hours or shorter.

[0099] In addition, the firing step (S20) can be fired at a temperature of one stage, but is preferably fired at a temperature of two or more stages. For example, when firing is performed at a temperature of two stages, it is preferred to have a first firing step (S21) of holding the temperature at 600°C to 800°C for more than 30 minutes and a second firing step (S22) of holding the temperature at a temperature of at least the first firing step and at a temperature of 1000°C or less.

[0100] When the two-stage calcination process is performed, in the first calcination process, the lithium compound is melted and sufficiently diffused in the nickel composite compound, thereby allowing lithium to react with the nickel composite compound, and in the second calcination process, crystal growth can be promoted.

[0101] It should be noted that the upper limit of the holding time at the firing temperature in the first firing process is not particularly limited as long as the scope that lithium can fully diffuse, for example, can be set to the degree below 5 hours. In addition, the holding time at the firing temperature in the second firing process is not particularly limited as long as the scope that can fully cause crystal growth, for example, can be set to more than 3 hours, preferably more than 5 hours and less than 24 hours.

[0102] [crush]

[0103] Although the sintering of the lithium nickel composite oxide obtained after the sintering step (S20) is suppressed, sometimes coarse particles are formed due to weak sintering and agglomeration. In such a case, pulverization can be performed. By pulverizing, the above-mentioned sintering and agglomeration can be eliminated, and the particle size distribution of the obtained lithium nickel composite oxide can be adjusted. The pulverization is performed using a pulverizing device such as a jet mill, a ball mill, or a wet ball mill, for example.

[0104] [Water Wash]

[0105] The calcined product of the lithium nickel composite oxide obtained after the calcination step (S20) can be washed with water as needed. By washing with water, the excess lithium remaining on the surface of the particles can be removed. In addition, the excess lithium can also be removed by washing with water, thereby controlling the Li / Me of the lithium nickel composite oxide to be in the range of 0.95 to 1.10.

[0106] 3. Lithium-ion secondary battery

[0107] The manufacturing method of the lithium-ion secondary battery of the present embodiment (hereinafter also referred to as "the manufacturing method of the secondary battery") comprises a lithium-ion secondary battery obtained by using a positive electrode, a negative electrode and a non-aqueous electrolyte, and the positive electrode is obtained using a positive electrode active material obtained by the above-mentioned manufacturing method. It should be noted that the secondary battery obtained by the manufacturing method of the present embodiment may, for example, have a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte, or may have a positive electrode, a negative electrode and a solid electrolyte. In addition, the secondary battery can be constructed using the same constituent elements as the known lithium-ion secondary battery.

[0108] Hereinafter, as an example of a method for manufacturing a secondary battery of the present embodiment, the constituent materials of a secondary battery using a non-aqueous electrolyte and a method for manufacturing the same are described. It should be noted that the embodiments described below are merely illustrative, and the method for manufacturing a secondary battery can be implemented in a manner that is based on the embodiments described in this specification and various changes and improvements are made based on the knowledge of those skilled in the art. In addition, the use of the secondary battery obtained by the manufacturing method of the present embodiment is not particularly limited.

[0109] (positive electrode)

[0110] The positive electrode includes the positive electrode active material. The positive electrode can be manufactured, for example, as follows. It should be noted that the method for manufacturing the positive electrode is not limited to the following example, and other methods can be used.

[0111] First, the positive electrode active material, the conductive material and the binder are mixed, and then activated carbon, a solvent for viscosity adjustment and the like are added as needed, and they are kneaded to make a positive electrode composite paste. It should be noted that the constituent materials of the positive electrode composite paste are not particularly limited, and materials equivalent to known positive electrode composite pastes can be used.

[0112] The mixing ratio of each material in the positive electrode composite paste is not particularly limited and can be appropriately adjusted according to the required performance of the secondary battery. The mixing ratio of the materials can be set to the same range as the known positive electrode composite paste of the secondary battery. For example, when the total mass of the solid component of the positive electrode composite excluding the solvent is set to 100 parts by mass, the content of the positive electrode active material can be set to 60 parts by mass or more and 95 parts by mass or less, the content of the conductive material can be set to 1 part by mass or more and 20 parts by mass or less, and the content of the binder can be set to 1 part by mass or more and 20 parts by mass or less.

[0113] As the conductive agent, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), carbon black materials such as acetylene black and Ketjen black, etc. can be used.

[0114] The binder (adhesive) plays the role of linking the active material particles together, and for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, polyacrylic acid, etc. can be used.

[0115] It should be noted that, as needed, a solvent for dispersing the positive electrode active material, the conductive material, and the activated carbon and dissolving the binder (binder) can be added to the positive electrode composite paste. As a solvent, an organic solvent such as N-methyl-2-pyrrolidone (NMP) can be used. In addition, activated carbon can be added to the positive electrode composite to increase the double electric layer capacity.

[0116] Next, the obtained positive electrode composite paste is applied to the surface of a current collector such as aluminum foil and dried to disperse the solvent, thereby producing a sheet-shaped positive electrode. If necessary, a roller press or the like can be used to pressurize the electrode to increase the electrode density. The sheet-shaped positive electrode can be cut into an appropriate size according to the target battery and used for battery production.

[0117] (negative electrode)

[0118] As the negative electrode, metallic lithium, lithium alloy, etc. can be used. In addition, as the negative electrode, a negative electrode formed as follows can be used, that is, a negative electrode active material capable of absorbing and releasing lithium ions is mixed with a binder, and a suitable solvent is added to form a paste-like negative electrode composite material, and the negative electrode composite material is applied to the surface of a metal foil collector such as copper, dried, and compressed as needed to increase the electrode density, thereby forming a negative electrode.

[0119] As the negative electrode active material, for example, powders of carbon materials such as natural graphite, artificial graphite, phenolic resin, etc., sintered organic compounds, coke, etc. can be used. As the negative electrode binder, similar to the positive electrode, fluorine-containing resins such as PVDF can be used. In addition, as a solvent for dispersing these active materials and binders, organic solvents such as N-methyl-2-pyrrolidone can be used.

[0120] (Diaphragm)

[0121] A separator is disposed between the positive electrode and the negative electrode. The separator is used to separate the positive electrode from the negative electrode and to retain the electrolyte. A thin film such as polyethylene or polypropylene having a large number of minute pores can be used.

[0122] (Non-aqueous electrolyte)

[0123] As the non-aqueous electrolyte, for example, a non-aqueous electrolyte solution can be used.

[0124] As the non-aqueous electrolyte, for example, a solution obtained by dissolving a lithium salt as a supporting salt in an organic solvent can be used. In addition, as the non-aqueous electrolyte, a solution in which a lithium salt is dissolved in an ionic liquid can be used. It should be noted that an ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is also liquid at room temperature.

[0125] As the organic solvent, one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate and trifluoropropylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, carbomethyl acetate and dipropyl carbonate, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran and dimethoxyethane, sulfur compounds such as ethyl methyl sulfone and butane sultone, phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc. can be used alone, or two or more thereof can be mixed and used.

[0126] As supporting salt, LiPF can be used 6 , LiBF 4 、LiClO 4 、LiAsF 6 、LiN(CF 3 SO 2 ) 2 and composite salts thereof, etc. Furthermore, the non-aqueous electrolyte may also contain a radical scavenger, a surfactant, a flame retardant, and the like.

[0127] In addition, as the non-aqueous electrolyte, a solid electrolyte can be used. The solid electrolyte has the property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.

[0128] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.

[0129] The oxide-based solid electrolyte is not particularly limited, and an electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. For example, an oxide-based solid electrolyte selected from lithium phosphate (Li 3 PO 4 )、Li 3 PO 4 N X 、LiBO 2 N X 、LiNbO 3 、LiTaO 3 , Li 2 SiO 3 , Li 4 SiO 4 -Li 3 PO 4 , Li4 SiO 4 -Li 3 VO 4 , Li 2 OB 2 O 3 -P 2 O 5 , Li 2 O-SiO 2 , Li 2 OB 2 O 3 -ZnO, Li 1+X Al X Ti 2-X (PO 4 ) 3 (0≤X≤1), Li 1+X Al X Ge 2-X (PO 4 ) 3 (0≤X≤1), LiTi 2 (PO 4 ) 3 , Li 3X La 2 / 3-X TiO 3 (0≤X≤2 / 3), Li 5 La 3 Ta 2 O 12 , Li 7 La 3 Zr 2 O 12 , Li 6 BaLa 2 Ta 2 O 12 , Li 3.6 Si 0.6 P 0.4 O 4 One or more of the following.

[0130] The sulfide-based solid electrolyte is not particularly limited, and for example, an electrolyte containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. As the sulfide-based solid electrolyte, for example, a sulfide-based solid electrolyte selected from Li 2 SP 2 S 5 , Li 2 S-SiS 2 、LiI-Li 2 S-SiS 2 、LiI-Li 2 SP 2 S5 、LiI-Li 2 SB 2 S 3 , Li 3 PO 4 -Li 2 S-Si 2 S. Li 3 PO 4 -Li 2 S-SiS 2 、LiPO 4 -Li 2 S-SiS、LiI-Li 2 SP 2 O 5 、LiI-Li 3 PO 4 -P 2 S 5 One or more of the following.

[0131] It should be noted that as the inorganic solid electrolyte, substances other than those mentioned above may also be used, for example, Li 3 N, LiI, Li 3 N-LiI-LiOH, etc.

[0132] The organic solid electrolyte is not particularly limited as long as it is a polymer compound showing ion conductivity, and for example, polyethylene oxide, polypropylene oxide, copolymers thereof, etc. can be used. In addition, the organic solid electrolyte may contain a supporting salt (lithium salt).

[0133] (Battery shape and structure)

[0134] The shape of the lithium ion secondary battery of the present embodiment composed of the positive electrode, the negative electrode and the non-aqueous electrolyte as described above can be made into various shapes such as cylindrical and stacked. Regardless of the shape, the lithium ion secondary battery is completed as follows, that is, the positive electrode and the negative electrode are stacked through the diaphragm to form an electrode body, the non-aqueous electrolyte is impregnated in the obtained electrode body, and the positive electrode collector is connected to the positive terminal leading to the outside and the negative electrode collector is connected to the negative terminal leading to the outside using a collector lead, and sealed in a battery box, thereby completing the lithium ion secondary battery. It should be noted that in the case of using a solid electrolyte, the solid electrolyte can also serve as a diaphragm.

[0135] (characteristic)

[0136] A secondary battery manufactured by using the above-mentioned positive electrode active material as a positive electrode can have a high battery capacity. The positive electrode active material obtained in a preferred embodiment is used, for example, in Figure 3In the case of the positive electrode of the 2032-type button-type battery CBA shown in the figure, a high initial discharge capacity of 185 mAh / g or more can be obtained within the range of charge and discharge voltage of 2.5 V to 4.3 V, and sometimes 190 mAh / g or more, or 200 mAh / g or more can be obtained depending on the manufacturing conditions. In addition, the above-mentioned button-type battery CBA can make the initial charge and discharge efficiency (efficiency) above 85%.

[0137] In addition, a secondary battery manufactured by using the above-mentioned positive electrode active material as a positive electrode can have high cycle characteristics. Figure 4 In the case of the positive electrode of the laminated battery LBA as shown, the capacity retention rate after 500 cycles can be made 60% or more, preferably 70% or more, more preferably 75% or more, and further preferably 80% or more.

[0138] [Example]

[0139] Hereinafter, the present invention will be further described in detail using the embodiments and comparative examples of the present invention, but the present invention is not limited to these embodiments. It should be noted that the analysis method of the metal contained in the positive electrode active material in the embodiments and comparative examples and the various evaluation methods of the positive electrode active material are as follows.

[0140] (1) Composition analysis: The composition was determined by ICP emission spectrometry.

[0141] (2) Ratio of the number of individual primary particles

[0142] After the lithium nickel composite oxide particles were embedded in the thermosetting resin, they were polished using a cross-section polisher (SM-09010 manufactured by JEOL Ltd.) The cross-section of the obtained particles was observed using a Schottky field emission scanning electron microscope (Ultra 55 manufactured by Carl Zeiss), and the number ratio of individual primary particles was evaluated from more than 100 particles.

[0143] (3) Average primary particle size

[0144] In the SEM observation image of the lithium nickel composite oxide particles (external shape), the major axis lengths of primary particles at 5 or more locations where the entire particle image is observed are measured by image analysis, and the average value is defined as the average primary particle size.

[0145] (4) Median diameter (D50)

[0146] The analysis was performed on a volume basis using a laser diffraction scattering type particle size analyzer (MICROTRAC HRA manufactured by NIKKISO CO., LTD.).

[0147] (5) Specific surface area

[0148] The specific surface area / pore distribution was measured by the BET method using nitrogen adsorption using a specific surface area / pore distribution measuring apparatus (Macsorb HM1200 series manufactured by Mountech Corporation).

[0149] (6) Amount of dissolved lithium

[0150] 20 g of the positive electrode active material was weighed and immersed in 100 ml of pure water at 25°C. After stirring for 30 minutes and standing for 10 minutes, the supernatant was titrated with an aqueous HCl solution. The titration was evaluated by the Warder method to calculate the content of lithium hydroxide (LiOH) and lithium carbonate (LiCO). 2 Co 3 ) and the sum of the lithium amounts contained in them is calculated as the eluted lithium amount.

[0151] (7) Crystal orientation evaluation using EBSD method

[0152] As a measuring device, a scanning electron microscope (SEM) equipped with a computer capable of analyzing crystal orientation (manufactured by Carl Zeiss: Ultra55) was used. The accelerating voltage of the electron beam irradiated to the sample to be measured was set to about 15 kV, and the current was set to about 20 nA.

[0153] In addition, for the region (measured surface) in the cross section of the measured sample where the crystal orientation was measured, orientation information in the x-axis and y-axis directions was obtained in a strip shape of 2.5 μm×12.5 μm, and the number of measurement points was set to 250,000 points in total.

[0154] It should be noted that in order to easily capture the scattered electron beams (Kikuchi lines) using a camera provided in the SEM device, the sample to be measured (specifically, the measured surface as a cross section) is tilted about 70° from the horizontal and arranged so that the scattered electron beams are irradiated toward the camera. The reference direction in the crystal orientation measurement is set to the z-axis direction with the depth direction of the cross section of the particle (the direction perpendicular to the paper surface) as the z-axis.

[0155] The scattered electron beam (Kikuchi line) is observed by a camera, and the data of the Kikuchi pattern observed by the camera is transmitted to a computer, and the Kikuchi pattern is analyzed to determine the crystal orientation. In this measurement, the region with a crystal orientation difference of less than 15° is set as a crystal plane, and the GROD method is used for analysis. It should be noted that the above analysis is implemented using commercially available EBSD analysis software (EBSD analysis software of Oxford Instruments: ProjectManager-Tango).

[0156] The above analysis is performed on arbitrary ten or more particles, and the number average of the average orientation differences of the particles is calculated as the average orientation difference of each crystal plane in the particle with respect to the reference direction.

[0157] (8) (003) peak and (104) peak intensity

[0158] The peak intensity of the (003) plane of the hexagonal layered structure corresponding to the diffraction peak height was calculated from the X-ray diffraction pattern measured by CuKα radiation using an XRD diffractometer (Empyrean, manufactured by Malvern Panalytical). (003) ] and the peak intensity of (104) plane [I (104) ]. It should be noted that the sample was filled in the groove of a circular glass holder with an outer diameter of 32 mmφ (a flat sample holder, groove inner diameter 24 mmφ, groove depth 0.5 mm, Malvern Panalytical model 9200 540 12391), fixed to a predetermined sample holder (Malvern Panalytical model 9430 018 13321) and provided for measurement.

[0159] (9) Evaluation of charging capacity, discharging capacity, and efficiency (battery characteristics)

[0160] [Production of button-type batteries]

[0161] like Figure 5 As shown, the button-type battery CBA is composed of a case CA and electrodes housed in the case CA.

[0162] The case CA includes a positive electrode case PC which is hollow and opened at one end and a negative electrode case NC arranged at the opening of the positive electrode case PC. When the negative electrode case NC is arranged at the opening of the positive electrode case PC, a space for accommodating electrodes is formed between the negative electrode case NC and the positive electrode case PC.

[0163] The electrodes are formed of a positive electrode PE, a separator SE1, and a negative electrode NE, which are stacked in this order and housed in a case CA such that the positive electrode PE contacts the inner surface of the positive electrode case PC and the negative electrode NE contacts the inner surface of the negative electrode case NC.

[0164] It should be noted that the box CA includes a gasket GA, which is used to restrict relative movement and fix the positive electrode case PC and the negative electrode case NC to maintain a non-contact state, that is, an electrically insulating state. In addition, the gasket GA also has a function of sealing the gap between the positive electrode case PC and the negative electrode case NC to isolate the inside and outside of the box CA in an airtight and liquid-tight manner.

[0165] The button-type battery CBA was prepared as follows: First, 52.5 mg of the obtained positive electrode active material, 15 mg of acetylene black and 7.5 mg of polytetrafluoroethylene (PTFE) resin were mixed and formed into a film having a diameter of 11 mm and a weight of about 75 mg to prepare a positive electrode PE, which was dried in a vacuum dryer at 100° C. for 12 hours.

[0166] A coin-type battery CBA was produced in a glove box of Ar atmosphere whose dew point was controlled at -60°C using the positive electrode PE, the negative electrode NE, the separator SE1, and the electrolyte solution.

[0167] As the negative electrode NE, lithium metal punched into a disk shape having a diameter of 13 mm was used.

[0168] As the separator SE1, a polyethylene porous film with a thickness of 25 μm was used. As the electrolyte, a 1 M LiClO 4 A mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 as a supporting electrolyte (manufactured by Toyama Pharmaceutical Industry Co., Ltd.) was used.

[0169] [Evaluation of charging capacity, discharging capacity and efficiency]

[0170] After making the button-type battery CBA, place it for about 12 hours. After the open circuit voltage OCV (open circuit voltage) stabilizes, set the current density at the positive electrode to 0.1 mA / cm 2 The capacity when charged to a cut-off voltage of 4.3 V was taken as the charge capacity. In addition, after a 1-hour rest after charging, the capacity when discharged to a cut-off voltage of 2.5 V was taken as the discharge capacity. Furthermore, the ratio of the discharge capacity to the charge capacity, i.e., the efficiency, was calculated.

[0171] Furthermore, the efficiency which is the ratio of the discharge capacity to the charge capacity is calculated.

[0172] (10) Cycle characteristics and gas generation

[0173] [Fabrication of laminated batteries]

[0174] like Figure 6 As shown, the laminated battery LBA has the following structure: the substance obtained by impregnating the positive electrode film PS, the separator SE2 and the negative electrode film NS with the electrolyte is sealed by the laminate LE. It should be noted that the positive electrode film PS is connected to the positive electrode tab TL, the negative electrode film NS is connected to the negative electrode tab NT, and the positive electrode tab PT and the negative electrode tab NT are exposed outside the laminate LA.

[0175] A slurry prepared by dispersing 20.0 g of the obtained positive electrode active material, 2.35 g of acetylene black, and 1.18 g of polyvinylidene fluoride in N-methyl-2-pyrrolidone (NMP) was prepared by placing the mixture on a plate at 1 cm 2 7.0 mg of positive electrode active material is coated on Al foil. Next, the material coated with the slurry containing the positive electrode active material on the Al foil is dried at 120°C in the atmosphere for 30 minutes to remove NMP. The Al foil coated with the positive electrode active material is cut into strips with a width of 66 mm and rolled at a load of 1.2 t to produce a positive electrode film. Then, the positive electrode film is cut into a rectangle of 50 mm × 30 mm, dried at 120°C for 12 hours in a vacuum dryer, and then used as the positive electrode film PS of the laminated battery LBA.

[0176] In addition, a negative electrode film NS was prepared by applying a negative electrode material paste, which was a mixture of graphite powder with an average particle size of about 20 μm and polyvinylidene fluoride, to a copper foil. A polyethylene porous film with a film thickness of 20 μm was used as the separator SE2, and a 1 M LiPF 6 A 3:7 mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (manufactured by Ube Industries, Ltd.) was used as a supporting electrolyte.

[0177] In a dry room whose dew point was controlled at -60°C, the stack of the positive electrode film PS, the separator SE2, and the negative electrode film NS was impregnated with an electrolyte solution and sealed by lamination LA to produce a laminated battery LBA.

[0178] [Cycle characteristics]

[0179] The cycle characteristics were evaluated by measuring the capacity retention rate after 500 cycles of charge and discharge. Specifically, the laminated battery LBA was charged and discharged at a current density of 0.3 mA / cm in a thermostatic chamber maintained at 25°C. 2 After conditioning, the battery was charged to a cut-off voltage of 4.2 V and then discharged to a cut-off voltage of 2.5 V after a 10-minute rest. This cycle was repeated for 5 cycles and then the battery was heated in a thermostatic chamber maintained at 45° C. at a current density of 2.0 mA / cm 2 The battery was charged to a cut-off voltage of 4.2 V, and then discharged to a cut-off voltage of 2.5 V after a 10-minute rest. This cycle was repeated 500 times, and the ratio of the adjusted discharge capacity of the 500th cycle to the discharge capacity of the first cycle, i.e., the capacity retention rate, was calculated and evaluated. It should be noted that for Example 11 and Comparative Example 8, the cut-off voltage during charging was set to 4.3 V.

[0180] [Example 1]

[0181] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 13.0 μm) obtained by a known method with a mass ratio of nickel, manganese and cobalt of Ni:Mn:Co=85.0:10.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, became 1.015. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0182] The raw material mixture was sintered by heating to 700° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 850° C. and holding the temperature for 8 hours.

[0183] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0184] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles reached 81.5%, that is, it was composed of a majority of single primary particles and a minority of secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.3 μm, and D50 was 2.6 μm. The evaluation results are shown in Tables 1 and 2.

[0185] [Example 2]

[0186] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.8 μm) having a mass ratio of nickel to cobalt of Ni:Co=95.0:5.0 obtained by a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide was obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0187] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0188] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C in a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours. The vacuum-dried lithium nickel composite oxide was crushed using a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles. It was confirmed that the Li / Me of the obtained positive electrode active material was 0.999.

[0189] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles reached 92.1%, that is, it was composed of a majority of single primary particles and a minority of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.3 μm, and D50 was 1.4 μm. The evaluation results are shown in Tables 1 and 2.

[0190] [Example 3]

[0191] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.8 μm) having a mass ratio of nickel to cobalt of Ni:Co=95.0:5.0 obtained by a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide was obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0192] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0193] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0194] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles reached 75.6%, that is, it was composed of a large number of single primary particles and a small number of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.5 μm, and D50 was 1.5 μm. The evaluation results are shown in Table 1 and Table 2.

[0195] [Example 4]

[0196] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel to manganese of Ni:Mn=95.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.025. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0197] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heated to 800° C. and maintained for 8 hours to perform sintering.

[0198] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0199] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide reached 83.6%, that is, it was composed of a majority of single primary particles and a minority of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.6 μm, and D50 was 2.1 μm. The evaluation results are shown in Tables 1 and 2.

[0200] [Comparative Example 1]

[0201] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 13.0 μm) obtained by a known method with a mass ratio of nickel, manganese and cobalt of Ni:Mn:Co=85.0:10.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, became 1.015. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0202] The raw material mixture was sintered by heating to 700° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen. The temperature was then further heated to 850° C. and held for 8 hours.

[0203] The fired lithium nickel composite oxide was processed by a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0204] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles was 5.6%, that is, almost composed of secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.5 μm, and D50 was 15.8 μm. The evaluation results are shown in Table 1 and Table 2.

[0205] [Comparative Example 2]

[0206] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.8 μm) having a mass ratio of nickel to cobalt of Ni:Co=95.0:5.0 obtained by a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide was obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0207] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen. The temperature was then further heated to 760° C. and held for 8 hours.

[0208] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C at a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours. The vacuum-dried lithium nickel composite oxide was processed using a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0209] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide was 0.2%, that is, almost composed of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.7 μm, and D50 was 7.7 μm. The evaluation results are shown in Table 1 and Table 2.

[0210] [Comparative Example 3]

[0211] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel to manganese of Ni:Mn=95.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.025. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0212] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heated to 800° C. and maintained for 8 hours to perform sintering.

[0213] The fired lithium nickel composite oxide was processed by a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0214] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide was 0.5%, that is, almost composed of secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.5μm, and D50 was 15.8μm. The evaluation results are shown in Table 1 and Table 2.

[0215] [Comparative Example 3]

[0216] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel to manganese of Ni:Mn=95.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.025. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0217] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heated to 800° C. and maintained for 8 hours to perform sintering.

[0218] The fired lithium nickel composite oxide was processed by a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0219] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide was 0.5%, that is, almost composed of secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.5μm, and D50 was 15.8μm. The evaluation results are shown in Table 1 and Table 2.

[0220] [Table 1]

[0221]

[0222] [Table 2]

[0223]

[0224] [Example 5]

[0225] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel, cobalt and aluminum of Ni:Co:Al=95.0:3.0:2.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0226] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0227] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C in a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours using a jet mill. The vacuum-dried lithium nickel composite oxide was crushed to obtain a positive electrode active material composed of lithium nickel composite oxide particles. It was confirmed that the Li / Me of the obtained positive electrode active material was 0.986.

[0228] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles reached 71.4%, that is, it was composed of a large number of single primary particles and a small number of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.0 μm, and D50 was 1.1 μm. The evaluation results are shown in Tables 3 and 4.

[0229] [Example 6]

[0230] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel, cobalt and aluminum of Ni:Co:Al=95.0:3.0:2.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0231] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0232] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0233] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of the lithium nickel composite oxide reached 62.0%, that is, it was composed of a large number of single primary particles and secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.0 μm, and D50 was 1.2 μm. The evaluation results are shown in Tables 3 and 4.

[0234] [Example 7]

[0235] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.7 μm) obtained by a known method with a mass ratio of nickel, cobalt and aluminum of Ni:Co:Al=82.0:15.0:3.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium contained in the raw material mixture, i.e., Li / Me, became 1.018. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0236] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 85% by volume and the balance being nitrogen, and then further heated to 810° C. and maintained for 8 hours to perform sintering.

[0237] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0238] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide reached 70.1%, that is, it was composed of a large number of single primary particles and a small number of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.9 μm, and D50 was 2.1 μm. The evaluation results are shown in Tables 3 and 4.

[0239] [Example 8]

[0240] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix a nickel composite oxide (D50 particle size: 6.2 μm) obtained by a known method with a mass ratio of nickel to aluminum of Ni:Al=95.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0241] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0242] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C in a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours. The vacuum-dried lithium nickel composite oxide was crushed using a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles. It was confirmed that the Li / Me of the obtained positive electrode active material was 0.976.

[0243] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles reached 81.6%, that is, it was composed of a majority of single primary particles and a small number of secondary particles. In addition, the average primary particle size of the positive electrode active material was 0.8 μm, and D50 was 0.9 μm. The evaluation results are shown in Tables 3 and 4.

[0244] [Example 9]

[0245] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.8 μm) having a mass ratio of nickel to aluminum of Ni:Al=95.0:5.0 obtained by a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide was obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0246] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0247] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0248] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide reached 56.8%, that is, it was composed of a large number of single primary particles and secondary particles. In addition, the average primary particle size of the positive electrode active material was 0.9 μm, and D50 was 1.2 μm. The evaluation results are shown in Table 3 and Table 4.

[0249] [Example 10]

[0250] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix nickel oxide (D50 particle size: 6.0 μm) obtained using a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.018. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained using a crystallization method.

[0251] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heated to 800° C. and maintained for 8 hours to perform sintering.

[0252] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0253] The obtained positive electrode active material was observed by SEM, and the results showed that the number ratio of single primary particles in the lithium nickel composite oxide particles reached 86.5%, that is, it was composed of a majority of single primary particles and a minority of secondary particles. Figure 1 In addition, the average primary particle size of the positive electrode active material was 2.1 μm, and D50 was 2.2 μm. The evaluation results are shown in Tables 3 and 4. In addition, an example of a GROD diagram of a particle cross section is shown in Figure 2 middle.

[0254] [Comparative Example 4]

[0255] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 6.0 μm) obtained by a known method with a mass ratio of nickel, cobalt and aluminum of Ni:Co:Al=95.0:3.0:2.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0256] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0257] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C at a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours. The vacuum-dried lithium nickel composite oxide was processed using a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0258] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide was 0.0%, that is, it was composed of only secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.1 μm, and D50 was 8.3 μm. The evaluation results are shown in Table 3 and Table 4.

[0259] [Comparative Example 5]

[0260] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) was used to thoroughly mix a nickel composite oxide (D50 particle size: 5.7 μm) obtained by a known method with a mass ratio of nickel, cobalt and aluminum of Ni:Co:Al=82.0:15.0:3.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, became 1.018. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0261] The raw material mixture was heated to 600° C. and maintained for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 85% by volume and the balance being nitrogen, and then further heated to 810° C. and maintained for 8 hours to perform sintering.

[0262] The fired lithium nickel composite oxide was processed by a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0263] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of the lithium nickel composite oxide was 0.0%, that is, it was composed only of secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.0 μm, and D50 was 8.0 μm. The manufacturing conditions and evaluation results are shown in Tables 3 and 4.

[0264] [Comparative Example 6]

[0265] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix a nickel composite oxide (D50 particle size: 6.2 μm) obtained by a known method with a mass ratio of nickel to aluminum of Ni:Al=95.0:5.0 and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium, i.e., Li / Me, was 1.020. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained by a crystallization method.

[0266] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heating to 760° C. and holding the temperature for 8 hours.

[0267] The calcined lithium nickel composite oxide was put into a beaker filled with pure water at 25°C at a concentration of 1500 g / L and washed with water for 15 minutes. It was then filtered and the obtained water-containing powder was vacuum dried at 190°C for 15 hours. The vacuum-dried lithium nickel composite oxide was processed using a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0268] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles was 0.0%, that is, it was composed of only secondary particles. In addition, the average primary particle size of the positive electrode active material was 0.8 μm, and D50 was 6.8 μm. The evaluation results are shown in Tables 3 and 4.

[0269] [Comparative Example 7]

[0270] A vibrating mixer (Willy A Bachofen (WAB) company model: TURBULA Type T2C) was used to fully mix nickel oxide (D50 particle size: 6.0 μm) obtained using a known method and lithium hydroxide to prepare a raw material mixture. In addition, the raw material mixture was weighed in such a manner that the ratio of the number of atoms of lithium (Li) to the number of atoms of metals other than lithium (Me), i.e., Li / Me, was 1.018. It should be noted that the nickel composite oxide is obtained by heat treating a nickel composite hydroxide obtained using a crystallization method.

[0271] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 3 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the remainder being nitrogen, and then further heating to 720° C. and holding the temperature for 8 hours.

[0272] The fired lithium nickel composite oxide was processed using a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0273] The obtained positive electrode active material was observed by SEM, and it was confirmed that the number ratio of primary particles alone in the lithium nickel composite oxide particles was 0.0%, that is, it was composed only of secondary particles. Figure 3 In addition, the average primary particle size of the positive electrode active material was 0.6 μm, and D50 was 7.4 μm. The evaluation results are shown in Tables 3 and 4. In addition, an example of a GROD diagram of a particle cross section is shown in Figure 4 middle.

[0274] [Table 3]

[0275]

[0276] [Table 4]

[0277]

[0278] [Example 11]

[0279] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) is used to thoroughly mix nickel composite oxide (D50 particle size: 12.8 μm) having a molar ratio of nickel, manganese and cobalt of Ni:Mn:Co=55.0:25.0:20.0 obtained using a known method, lithium hydroxide and zirconium oxide to prepare a raw material mixture. At this time, the raw material mixture is weighed in such a way that the ratio of the number of atoms of zirconium (Zr) in the zirconium oxide is 0.5 at% relative to the total number of atoms of nickel, manganese and cobalt. In addition, the raw material mixture is weighed in such a way that the ratio of the number of atoms of lithium (Li) and metal (Me) other than lithium contained in the raw material mixture, i.e., Li / Me, is 1.025. It should be noted that the nickel composite oxide is obtained by heat treating the nickel composite hydroxide obtained using a crystallization method.

[0280] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 2 hours in an oxygen-containing atmosphere having an oxygen concentration of 85% by volume and the balance being nitrogen, and then further heating to 970° C. and holding the temperature for 5 hours.

[0281] The fired lithium nickel composite oxide was pulverized by a jet mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0282] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide reached 73.0%, that is, it was composed of a large number of single primary particles and a small number of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.7μm, and D50 was 1.8μm. The evaluation results are shown in Table 5 and Table 6.

[0283] [Example 12]

[0284] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) is used to thoroughly mix a nickel composite oxide (D50 particle size: 4.5 μm) having a mass ratio of nickel, manganese and cobalt of Ni:Mn:Co=85.0:10.0:5.0 obtained using a known method, lithium hydroxide and zirconium oxide to prepare a raw material mixture. At this time, the raw material mixture is weighed in such a way that the ratio of the number of atoms of zirconium (Zr) in the zirconium oxide is 0.5 at% relative to the total number of atoms of nickel, manganese and cobalt. In addition, the raw material mixture is weighed in such a way that the ratio of the number of atoms of lithium (Li) and metals (Me) other than lithium, i.e., Li / Me, is 1.02. It should be noted that the nickel composite oxide is obtained by heat treating the nickel composite hydroxide obtained using a crystallization method.

[0285] The raw material mixture was heated to 700° C. and maintained for 2 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume and the balance being nitrogen, and then further heated to 900° C. and maintained for 10 hours to perform sintering.

[0286] The fired lithium nickel composite oxide is pulverized to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0287] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide reached 52.1%, that is, it was composed of a large number of single primary particles and secondary particles. In addition, the average primary particle size of the positive electrode active material was 2.4μm, and D50 was 7.9μm. The evaluation results are shown in Table 5 and Table 6.

[0288] [Example 13]

[0289] During the calcination, a positive electrode active material was obtained in the same manner as in Example 12 except that the temperature was raised to 700° C. and maintained for 2 hours, and then further raised to 870° C. and maintained for 10 hours.

[0290] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the lithium nickel composite oxide particles was 36.0%, that is, the single primary particles were contained in a considerable ratio in the secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.4 μm, and D50 was 7.4 μm. The evaluation results are shown in Tables 5 and 6.

[0291] [Comparative Example 8]

[0292] A vibrating mixer (model: TURBULA Type T2C manufactured by Willy A Bachofen (WAB) Co.) is used to thoroughly mix a nickel composite oxide (D50 particle size: 12.8 μm) obtained by a known method in which the mass ratio of nickel, manganese and cobalt is Ni:Mn:Co=55.0:25.0:20.0, lithium hydroxide and zirconium oxide to prepare a raw material mixture. At this time, the raw material mixture is weighed in such a way that the ratio of the number of atoms of zirconium (Zr) in the zirconium oxide is 0.5 at% relative to the total number of atoms of nickel, manganese and cobalt. In addition, the raw material mixture is weighed in such a way that the ratio of the number of atoms of lithium (Li) and metals (Me) other than lithium, i.e., Li / Me, is 1.025. It should be noted that the nickel composite oxide is obtained by heat treating the nickel composite hydroxide obtained by the crystallization method.

[0293] The raw material mixture was sintered by heating to 600° C. and holding the temperature for 2 hours in an oxygen-containing atmosphere having an oxygen concentration of 85% by volume and the balance being nitrogen, and then further heating to 950° C. and holding the temperature for 7 hours.

[0294] The fired lithium nickel composite oxide was pulverized by a hammer mill to obtain a positive electrode active material composed of lithium nickel composite oxide particles.

[0295] The obtained positive electrode active material was observed by SEM, and the result confirmed that the number ratio of the single primary particles in the particles of lithium nickel composite oxide was 0.6%, that is, almost composed of secondary particles. In addition, the average primary particle size of the positive electrode active material was 1.9 μm, and D50 was 12.5 μm. The manufacturing conditions and evaluation results are shown in Table 5 and Table 6.

[0296] [Table 5]

[0297]

[0298] [Table 6]

[0299]

[0300] (Evaluation results)

[0301] As shown in Tables 1, 3, and 5, in the positive electrode active materials of all embodiments, the average orientation difference of each crystal plane in the particle relative to the reference direction is within 0.70°. In addition, in the positive electrode active materials of the embodiments, D50 is less than 10 μm, and the average primary particle size is greater than 0.3 μm, and at least 36% of the particles are composed of single primary particles in terms of number ratio.

[0302] On the other hand, in the positive electrode active material of the comparative example, the average orientation difference of each crystal plane in the particle relative to the reference direction is more than 0.73°, and it is believed that more strain is accumulated in the particle compared with the positive electrode active material of the embodiment. In addition, in the positive electrode active material of the comparative example, the number ratio of the single primary particles is less than 5.6%, that is, the ratio of the secondary particles is high, and it is composed of polycrystalline particles.

[0303] In addition, as shown in Tables 2, 4, and 6, if the embodiments and comparative examples with the same composition are compared respectively (for example, Embodiment 1 and Comparative Example 1 in Table 2, Embodiment 5 and Comparative Example 4 in Table 4, etc.), it can be seen that compared with the comparative examples, all embodiments have high capacity retention rates and improved cycle characteristics.

[0304] Industrial Applicability

[0305] In this embodiment, a positive electrode active material for a lithium ion secondary battery having high thermal stability and excellent battery characteristics can be obtained by an industrial production method. The lithium ion secondary battery is suitable for power sources of small portable electronic devices (notebook personal computers, mobile terminals, etc.) that generally require high capacity.

[0306] In addition, the secondary battery using the positive electrode active material of this embodiment has excellent thermal stability and capacity compared with the battery using the positive electrode active material of the conventional lithium nickel oxide, so it can be miniaturized and is suitable as a power source for electric vehicles with limited mounting space.

[0307] Furthermore, the secondary battery using the positive electrode active material of this embodiment can be used not only as a power source for electric vehicles driven purely by electric energy, but also as a power source for so-called hybrid vehicles used in conjunction with a combustion mechanism such as a gasoline engine or a diesel engine, or as a stationary storage battery.

[0308] It should be noted that the technical scope of the present invention is not limited to the forms described in the above-mentioned embodiments, etc. Sometimes one or more of the elements described in the above-mentioned embodiments, etc. may be omitted. In addition, the elements described in the above-mentioned embodiments, etc. may be appropriately combined. In addition, within the scope permitted by law, the contents of all documents cited in Japanese Patent Application Nos. 2019-157719, 2019-157720 and this specification, which are Japanese patent applications, are cited as part of the description herein.

[0309] Explanation of symbols

[0310] CBA…button-type battery, PE…positive electrode (electrode for evaluation), NE…negative electrode, SE1…separator, GA…gasket, WW…corrugated washer, PC…positive electrode case, NC…negative electrode case, LBA…laminated battery (laminated battery), PS…positive electrode sheet, NS…negative electrode sheet, SE2…separator, AS…aluminum laminate sheet, TL…tab lead.

Claims

1. A positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel composite oxide, wherein the lithium nickel composite oxide has a hexagonal layered structure and is composed of a single primary particle or a single primary particle and secondary particles formed by agglomeration of a plurality of primary particles, The metal elements constituting the lithium nickel composite oxide include lithium (Li) and nickel (Ni) and optionally include at least one element M (M) selected from the group consisting of Co, Mn, Al, V, Mg, Mo, Ca, Cr, Zr, Ti, Nb, Na, K, W, Fe, Zn, B, Si, P and Ta, and the amount ratio of the metal elements is represented by Li:Ni:M=a:b:c, wherein, 0.95≤a≤1.10, 0.30≤b≤1.00, 0.00≤c≤0.70, b+c=1, The cross section of the particle contained in the positive electrode active material has one or more crystal planes, and the average orientation difference of the crystal planes with respect to a reference direction measured by Electron Backscatter Diffraction (EBSD) method is within 0.7°. 2 . The positive electrode active material for lithium ion secondary batteries according to claim 1 , wherein the number ratio of the single primary particles is 30% or more relative to the entire particles.

3. The positive electrode active material for lithium ion secondary battery according to claim 1 or 2, wherein the (003) diffraction peak intensity I is obtained by X-ray diffraction measured using Cu-kα rays as an X-ray source and a flat sample holder of a Bragg-Brentano optical system. (003) and (104) diffraction peak intensity I (104) The ratio of I (003) / I (104) 2.0 or above. 4 . The positive electrode active material for a lithium ion secondary battery according to claim 1 , wherein a volume-based median diameter D50 is 10 μm or less, and an average primary particle size of the lithium nickel composite oxide is 0.3 μm or more.

5. The positive electrode active material for lithium ion secondary battery according to claim 1 or 2, wherein the specific surface area determined by nitrogen adsorption method is 1.0 m 2 / g above 5.0m 2 / g or less. 6 . A lithium ion secondary battery comprising at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode comprises the positive electrode active material for a lithium ion secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Lithium transition metal oxide compound for lithium secondary battery positive electrode active material, its manufacturing method and secondary battery using it

    JP2001243949A

  • Cathode active substance for nonaqueous secondary battery and cathode

    JP2004355824A

  • Method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery

    JP2017188444A

  • Nonaqueous electrolyte secondary battery

    WO2017169129A1

  • Plate-shaped particles for positive electrode material of lithium secondary batteries, lithium secondary battery positive electrode active material films, manufacturing method therefor, lithium secondary battery positive electrode active material man

    CN102239588A